Introduction to crystallography - Sands, Donald, 1929- (Dover classics of science and mathematics., 1993)
Concise explanation of the logical development of basic crystallographic concepts. Extensive discussion of crystals and lattices, symmetry, crystal systems and geometry, x-ray diffraction, determination of atomic positions, and more. Well-chosen selection of problems, with answers. Ideal for crystallography course or as supplement to physical chemistry courses. 114 illustrations.